Fluktuasi Populasi Serangga Wereng Batang Coklat (Nilaparvata lugens) Pada Lahan Sawah Di Kabupaten Kerawang Jawa Barat - Martua Suhunan Sianipar (Agrologia, 2018)
Brown Planthopper (Nilaparvata lugens Stal.) is a main pest of paddy. The purpose of this research is to study the population of Brown Planthopper and the natural enemy. The method of this research using survey. Survey was conducted in three experimental plots at JatisariSubdistrict, Karawang District, West Javaand in the greenhouse of the Department of Plant Pests and Deseases, Faculty of Agriculture,  Universitas Padjadjaran. The sample were collected by systematically diagonal using yellow stiky trap and manually or visual counting. The result showed population fluctuation BPH below the economy line where is temperature, humidity and rainfall did not significantly effect to the BPH population. It was indicated by the regression analysis of each temperature Y= (- 24.225 + 1.008 X1 ; R2 =0,020; P/Sign = 0.660),  Humidity  (Y=- 32.337 + 0.424 X2; R2  = 0,124; P/ Sign  = 0.261) and Rainfall (Y=1.707 + 0.090 X3 ; R2  = 0.050; P/ Sign = 0.487). There is a relation between temperature, humidity and rainfall to BPH (Y = - 123 + 2.685 T + 0.649 RH - 0.14 CH; R2 = 0.236; P/ Sign = 0.516) dit not significantly because as the value of significance (P = Sign)  > 0.05.8. The diversity index was moderate 1.88